Some Random Fixed-Point Theorems for Weakly Contractive Random Operators in a Separable Banach Space - Kenza Benkirane; Abderrahim EL Adraoui; El Miloudi Marhrani (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to prove a common random fixed-point and some random fixed-point theorems for random weakly contractive operators in separable Banach spaces. A random Mann iterative process is introduced to approximate the fixed point. Finally, the main result is supported by an example and used to prove the existence and the uniqueness of a solution of a nonlinear stochastic integral equation system.